Telomere length as a biomarker of aging and diseases - Guzonjić, Azra; Sopić, Miron; Ostanek, Barbara; Kotur-Stevuljević, Jelena (Archives of Pharmacy, 2022)
As research related to healthspan and lifespan has become a hot topic, the necessity for a reliable and practical biomarker of aging (BoA), which can provide information about mortality and morbidity risk, along with remaining life expectancy, has increased. The chromosome terminus non-coding protective structure that prevents genomic instability is called a telomere. The continual shortening of telomeres, which affects their structure as well as function, is a hallmark of agedness. The aforementioned process is a potential cause of age-related diseases (ARDs), leading to a bad prognosis and a low survival rate, which compromise health and longevity. Hence, studies scrutinizing the BoAs often include telomere length (TL) as a prospective candidate. The results of these studies suggest that TL measurement can only provide an approximate appraisal of the aging rate, and its implementation into clinical practice and routine use as a BoA has many limitations and challenges. Nevertheless, measuring TL while determining other biomarkers can be used to assess biological age. This review focuses on the importance of telomeres in health, senescence, and diseases, as well as on summarizing the results and conclusions of previous studies evaluating TL as a potential BoA.